A Gold Nanocage Probe Targeting Survivin for the Diagnosis of Pancreatic Cancer - Lina Song; Shuai Ren; Yali Yue; Ying Tian; Zhongqiu Wang (MDPI AG, 2023)
In this paper, Au nanocages (AuNCs) loaded with the MRI contrast agent gadolinium (Gd) and capped with the tumor-targeting gene survivin (Sur-AuNC•Gd-Cy7 nanoprobes) were designed and applied as a targeted imaging agent for pancreatic cancer. With its capacity to transport fluorescent dyes and MR imaging agents, the gold cage is an outstanding platform. Furthermore, it has the potential to transport different drugs in the future, making it a unique carrier platform. The utilization of Sur-AuNC•Gd-Cy7 nanoprobes has proven to be an effective means of targeting and localizing survivin-positive BxPC-3 cells within their cytoplasm. By targeting survivin, an antiapoptotic gene, the Sur-AuNC•Gd-Cy7 nanoprobe was able to induce pro-apoptotic effects in BxPC-3 pancreatic cancer cells. The biocompatibility of AuNCs•Gd, AuNCs•Gd-Cy7 nanoparticles, and Sur-AuNC•Gd-Cy7 nanoprobes is evaluated through the hemolysis rate assay. The stability of AuNCs•Gd, AuNCs•Gd-Cy7 nanoparticles, and Sur-AuNC•Gd-Cy7 nanoprobes was evaluated by determining their hydrodynamic dimensions following storage in different pH solutions for a corresponding duration. Excellent biocompatibility and stability of the Sur-AuNC•Gd-Cy7 nanoprobes will facilitate their further utilization in vivo and in vitro. The surface-bound survivin plays a role in facilitating the Sur-AuNC•Gd-Cy7 nanoprobes' ability to locate the BxPC-3 tumor. The probe was modified to incorporate Gd and Cy7, thereby enabling the simultaneous utilization of magnetic resonance imaging (MRI) and fluorescence imaging (FI) techniques. In vivo, the Sur-AuNC•Gd-Cy7 nanoprobes were found to effectively target and localize survivin-positive BxPC-3 tumors through the use of MRI and FI. After being injected via the caudal vein, the Sur-AuNC•Gd-Cy7 nanoprobes were found to accumulate effectively in an in situ pancreatic cancer model within 24 h. Furthermore, these nanoprobes were observed to be eliminated from the body through the kidneys within 72 h after a single injection. This characteristic is crucial for a diagnostic agent. Based on the aforementioned outcomes, the Sur-AuNC•Gd-Cy7 nanoprobes have significant potential advantages for the theranostic treatment of pancreatic cancer. This nanoprobe possesses distinctive characteristics, such as advanced imaging abilities and specific drug delivery, which offer the possibility of enhancing the precision of diagnosis and efficacy of treatment for this destructive illness.